2012
DOI: 10.1177/0276146712448193
|View full text |Cite
|
Sign up to set email alerts
|

Are Consumers Acting Fairly Toward Companies?

Abstract: Fairness is an important component of all marketing exchange. While previous literature has focused on companies’ fair actions toward consumers, this article examines fair actions of consumers toward companies. Through a series of experiments, the authors investigate consumer fairness in the context of a pay-what-you-want pricing scheme. Results show that some consumers act fairly toward companies, even if they have no obligation to do so. For such consumers, there seems to be a self-signaling motive, in that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(7 citation statements)
references
References 65 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…Nelson [88] and Jang and Chu [23], who showed that consumers pay higher prices in PWYW because they care more about their self-image rather than their loss to the companies. Accordingly, fairness is attributed to the determining person instead of to the price itself.…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
“…Nelson [88] and Jang and Chu [23], who showed that consumers pay higher prices in PWYW because they care more about their self-image rather than their loss to the companies. Accordingly, fairness is attributed to the determining person instead of to the price itself.…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
“…Likewise, the results of the present study suggest that altruistic considerations are of less importance than other influential determinants to pricing decisions under PWYW circumstances. Jang and Chu [19] discussed the comparably low influence of SNC, stating that injunctive norms (i.e., what ought to be done and thus representing the construct SNC) are not the predominant social norm in a PWYW context. The present study confirmed this finding, as SNC belonged to the influential cluster with a relatively low importance to PWYW decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the relative novelty of PWYW, numerous examinations of the pricing mechanism in terms of associated fairness considerations [19], its competitiveness [11] [20] [21], or related social norms [7] [ 16] have recently been published. However, no holistic composition of the underlying influences of a PWYW decision has been developed yet.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the willingness to pay in the present experiment was not used to gain insights into total revenues for the travelling mug compared to alternative pricing mechanisms. However, the interpretability of group differences is not affected by this limitation and has been used in other studies [13]. Social Norm Compliance was measured on a scale consisting of three items, ( Table 1) on five-point Likert scales, ranging from "1: totally disagree" to "5: totally agree".…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, altruism and loyalty were found to be important contributors in one of the three studies. Henceforward, those seven factors were mainly accepted and assumed for further research [13] [14].…”
Section: Introductionmentioning
confidence: 99%